An evaluation of SecondBite®'s FoodMate®, a nutrition education and skill‐building program aimed at reducing food insecurity. (6th October 2019) - Stephens, Lena D.; Smith, Geoff; Olstad, Dana Lee; Ball, Kylie
Abstract: Issue addressed: Enhancing food skills and nutrition knowledge may help promote healthy eating among people who are food insecure. FoodMate ® by SecondBite ®, an 8‐week nutrition education and food hamper program, focuses on developing food skills and independence among Australians at risk of/experiencing food insecurity. This study aimed to explore participants' perceptions of and experiences with FoodMate ® over a long‐term (up to 2 years) follow‐up. Methods: For evaluation purposes, SecondBite ® previously collected data from participants prior to (T1) and following completion (T2) of FoodMate ® . This paper reports results from semi‐structured telephone interviews conducted in a follow‐up study (2016/2017, T3) among 19 adults enrolled in FoodMate ® programs delivered in Victoria and New South Wales within the previous two years. Data were analysed using inductive thematic analysis of responses to T3 open‐ended questions, and descriptive analysis of closed‐ended question responses (T1 vs T2 vs T3). Results: Major qualitative themes included program enjoyment; perceived positive long‐term program impact on participants' eating and related attitudes and skills; barriers to cooking; suggested program modifications; and impact on others. In descriptive quantitative analyses, participants' diet; confidence to cook using basic ingredients, follow simple recipes and try new foods; cooking and food‐related skills; social engagement and life satisfaction all improved between T1 and T3. Conclusions: Overall, FoodMate ® was well‐received and associated with long‐term positive changes in a range of outcomes. Wider implementation among vulnerable groups should be considered. So what?: Future health promotion initiatives could adopt FoodMate ® to increase food skills and knowledge among adults experiencing food insecurity. Summary: This study explored participants' perceptions of and experiences with FoodMate ® by SecondBite ®, a nutrition education program focused on developing food skills and independence among Australians at risk of/experiencing food insecurity. Long‐term positive changes in confidence, cooking and food‐related skills; social engagement; life satisfaction; and dietary intake were observed.